Pemaknaan siswa terhadap kegiatan pesantren kilat dalam meningkatkan ketaatan beribadah - Sriwahyuni, Ranti Ayu; Fakhruddin, Agus (TA`DIBUNA, 2025)
The pesantren kilat program is held during Ramadan to deepen students' understanding of religion and foster habitual worship. This study aims to explore students' perceptions of the pesantren kilat program and its impact on their worship practices. Using a qualitative approach with a phenomenological method, data were collected through Focus Group Discussions (FGD) involving 28 sixth-grade students from SDN Cukanggenteng 01 with more than 85% attendance. The findings reveal that students perceive the pesantren kilat as a meaningful collective experience, encouraging increased adherence to mahdhah worship practices such as prayer and Quran recitation, and ghairu mahdhah activities like helping parents and giving charity. The supportive Ramadan atmosphere at school and the presence of dedicated religious teachers foster a sense of comfort and motivation for consistent worship. In conclusion, the pesantren kilat program not only enhances worship adherence but also provides a meaningful experience in shaping students' religious character. AbstrakProgram pesantren kilat merupakan kegiatan yang diadakan selama bulan Ramadhan untuk memperdalam pemahaman agama dan membentuk kebiasaan beribadah siswa. Penelitian ini bertujuan untuk mengungkap pemaknaan siswa terhadap kegiatan pesantren kilat dan pengaruhnya terhadap ketaatan beribadah. Menggunakan pendekatan kualitatif dengan metode fenomenologi, data diperoleh melalui Focus Group Discussion (FGD) dengan 28 siswa kelas 6 SDN Cukanggenteng 01 yang memiliki tingkat kehadiran kegiatan pesantren kilat di atas 85%. Hasil penelitian menunjukkan bahwa siswa memaknai pesantren kilat sebagai pengalaman kolektif yang membangun, mendorong ketaatan beribadah mahdhah seperti shalat dan mengaji, serta ghairu mahdhah seperti membantu orang tua dan bersedekah. Suasana Ramadhan di sekolah yang kondusif dan dukungan guru ngaji menciptakan rasa nyaman serta motivasi bagi siswa untuk beribadah lebih konsisten. Kesimpulannya, pesantren kilat tidak hanya meningkatkan ketaatan beribadah, tetapi juga memberikan pengalaman bermakna dalam membentuk karakter religius siswa.